2021
DOI: 10.1080/14733285.2021.1913482
|View full text |Cite
|
Sign up to set email alerts
|

Recognising and exploring children’s geographies in school geography

Abstract: This article draws on the author's doctoral research to examine the relationships between children's geographies in different spaces of geographical thought in Englandgeography in and of everyday life, geography as an academic discipline and geography as a school subject. It begins by setting out how children's geographies have largely been omitted from school geography due to complex reasons including the impact of governmental policy on teaching and teacher education, and the public accountability of schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The research found that the young people in the study navigated multiple, sometime contradictory, social spaces when constructing and representing themselves and their identities in London; that the young people imagined London as a jigsaw of territories with distinct social rules existing in different spaces and places within the city; and that London was perceived by the young people who participated in the research as a place of opportunity and hope, but also as a place of inequality and injustice (Hammond, 2021(Hammond, , 2022. Analysis showed that with regards to identity, the young people particularly focused on the themes of religion; sex, sexuality and gender; voice; and their experiences of feeling or being British, or not (Hammond, 2021(Hammond, , 2022. The extracts discussed below focus specifically on the young people's narratives analysed as relating to religion and identity.…”
Section: Research Findingsmentioning
confidence: 98%
See 3 more Smart Citations
“…The research found that the young people in the study navigated multiple, sometime contradictory, social spaces when constructing and representing themselves and their identities in London; that the young people imagined London as a jigsaw of territories with distinct social rules existing in different spaces and places within the city; and that London was perceived by the young people who participated in the research as a place of opportunity and hope, but also as a place of inequality and injustice (Hammond, 2021(Hammond, , 2022. Analysis showed that with regards to identity, the young people particularly focused on the themes of religion; sex, sexuality and gender; voice; and their experiences of feeling or being British, or not (Hammond, 2021(Hammond, , 2022. The extracts discussed below focus specifically on the young people's narratives analysed as relating to religion and identity.…”
Section: Research Findingsmentioning
confidence: 98%
“…This is because the model suggests that teachers should consider the children they teach before anything else. In doing so, the model represents children as children, and not students (their given identity in school), thus appearing to celebrate the child as a social actor who exists beyond the school gate, and who has their own experiences, imaginations and 'everyday' knowledge of the world (Hammond, 2022). Following this, the model expresses that the teacher should critically consider the purposes of (a geographical) education in the place and time-space they exist within and contribute to, before making decisions about curriculum (what to teach) and pedagogy (how to teach it).…”
Section: Why Ask 'Who Are the Children We Teach?'mentioning
confidence: 99%
See 2 more Smart Citations
“…These interventions are partly curricular, giving young people access to recent developments in the discipline. They also echo Yarwood and Tyrrell’s (2012) calls for informing teaching and research, and Hammond (2021a) arguments about the importance of relationships between children’s everyday lives and geographical education to encourage ‘dialogic conversation’ (Hammond, 2021b: 13) across pedagogy, curriculum and research. In sharp contrast to previous characterisations of the field of geography education research as unfunded, there has been an increase in funded research in the field across RCUK (Research Councils United Kingdom), GCRF (Global Challenges Research Fund), EU (European Union) and beyond, for example, fostering collaborations between geography education researchers and artists (Walshe et al, 2020) and geography teacher educators internationally (Uhlenwinkel et al, 2016).…”
Section: Interactions and Relationshipsmentioning
confidence: 98%